Smart Energy-intelligent Solutions for Residential Buildings. (2015) - Marinescu, Cristina-Mihaela
Abstract: The main objective of this paper is to create a computing environment available on-line that meets the criteria for the efficient use of electricity in homes, while integrating the effects of environmental, economic and social. The developed system is a basis for conceptualizing, demonstrating and evaluating a variety of innovative end consumer services and their user interface paradigms. Now to decide buying a product the consumer is not able to compare - the lack of information, time, difficulty several criteria (including the one on energy efficiency and energy costs for the life cycle are very important) and therefore the price is the only element of decision. In order to make a final decision right, but he should be informed and educated on energy consumption to process and interpret the information.